Advances on practical applications of agents and multiagent systems 9th International Conference on Practical Applications of Agents and Multiagent Systems - International Conference on Practical Applications of Agents and Multiagent Systems Salamanca, Spain) 2011; Demazeau, Yves.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
IPAAMS, the International Conference on Practical Applications of Agents and Multi-Agent Systems is the international yearly tribune to present, to discuss, and to disseminate the latest developments and the most important outcomes related to real-world applications. It provides a unique opportunity to bring multi-disciplinary experts, academics and practitioners together to exchange their experience in the development of Agents and Multi-Agent Systems.   This volume presents the papers that have been accepted for the 2011 edition. These articles capture the most innovative results and this year?s trends: Finance and Trading, Information Systems and Organisations, Leisure Culture and Interactions, Medicine and Cloud Computing, Platforms and Adaptation, Robotics and Manufacturing, Security and Privacy, Transports and Optimisation paper.
Information and Organisations -- Robotics and Manufacturing -- Security and Privacy -- Platforms and Adaption -- Transport and Optimisation -- Leisure, Culture, Interactions -- Medicine and Cloud Computing -- Finance and Trading.
International conference proceedings.
Electronic reproduction.
Keywords: Intelligent agents (Computer software) -- Congresses; Electronic books